Compare the Intra–Operative Hemodynamics and the Perioperative Analgesic Efficacy of Superficial Sapb, to Deep SAPB, and to Thoracic Epidural Analgesia in Thoracotomies - Imran Tahir, Muhammad Zia, Hafiz Muhammad Waseem Yaseen, Aroob Zaki Khawaja, Shumyala Maqbool (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pain management following thoracotomy is still difficult because of its severity and complications. SAPB is getting popular as a procedure to replace TEA in the management of postoperative pain. Objective: The aim of this study was to compare the intraoperative effectiveness and safety of perioperative analgesic effect of superficial SAPB, deep SAPB, and TEA in patients undergoing thoracic surgeries. Material and Methods: This randomized controlled trial was performed on 60 patients undergoing thoracotomy at the Department of Surgery, Civil Hospital Bahawalpur, from January to June 2022. Patients were randomized into three groups: SAPB were defined as superficial SAPB, deep SAPB, and TEA. Intraoperative systolic and diastolic BP, postoperative pain scores at 1, 6 and 12 hours,heart rate, time to first rescue analgesia, total postoperative analgesia, duration of surgery, and hospital stay were key outcomes. The data were analysed using one-way ANOVA and Tukey’s post hoc test, p ≤ 0.05 was deemed to be significant. Results: Mean age was 41 (±13.72) years and mean BMI was 24.44 (±3.18). There differences among groups was insignificant (p > 0.05) in intraoperativeheart rate or BP. Diastolic blood pressure was significantly different (p = 0.030). There were no significant differences in each group with respect to postoperative pain scores, time to first rescue analgesic and total analgesic consumption (p > 0.05). Duration of surgery and hospital stay to recovery outcomes were also comparable (p > 0.05). Conclusion: Both superficial and deep SAPB provide comparable analgesic efficacy and hemodynamic stability to TEA in thoracic surgeries. SAPB offers a safe and effective alternative, particularly for patients with contraindications to TEA. Keywords: Thoracic Epidural, Analgesia, Thoracotomy, Postoperative Pain, Serratus Anterior Plane Block,Analgesic Efficacy, Hemodynamic Stability